Answer : The sixth term in the binomial expression is, [tex]^{10}C_5a^{5}b^{5}[/tex]
Step-by-step explanation :
The general formula to calculate the term of binomial expression is:
[tex]T_(r+1)=^nC_ra^{(n-r)}b^r[/tex]
where,
(r+1) = number of term
As we are given the binomial expression :
[tex](5y+3)^{10}[/tex]
For sixth term :
a = 5y
b = 3
n = 10
As, r + 1 = 6
So, r = 6 - 1
r = 5
Now put all the given values in the above formula, we get:
[tex]T_(r+1)=^nC_ra^{(n-r)}b^r[/tex]
[tex]T_(5)=^{10}C_5a^{10-5}b^5[/tex]
[tex]T_(5)=^{10}C_5a^{5}b^{5}[/tex]
Thus, the sixth term in the binomial expression is, [tex]^{10}C_5a^{5}b^{5}[/tex]